2017
DOI: 10.1371/journal.pntd.0005980
|View full text |Cite
|
Sign up to set email alerts
|

Reappraisal of Leishmanin Skin Test (LST) in the management of American Cutaneous Leishmaniasis: A retrospective analysis from a reference center in Argentina

Abstract: Leishmania (Viannia) braziliensis is the species most frequently implicated with cutaneous and mucosal leishmaniasis in the Americas; its diagnosis is based on the identification of amastigotes in lesions, which is limited by low parasite burden. Leishmanin Skin Test (LST) is a support tool for diagnosis, based on delayed type hypersensitivity responses to Leishmania antigens injected intradermally, used in endemic areas as a complement to diagnosis. A retrospective analysis of individuals evaluated for their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 24 publications
(25 reference statements)
2
22
0
1
Order By: Relevance
“…As in our study PCR assays have been carried out from smears' DNA, the molecular results were highly dependent on the samples collected and prepared for microscopy; and because P1+ smears had the lowest proportion of positive PCR (Figure 3), the importance of considering LST as a complementary diagnostic tool is highlighted. In a previous study, our group has shown that the ratio of positive LST to positive smear was ³ 1 and maintained across age groups, 19 supporting its diagnostic ability and suggesting that within an adequate epidemiologic frame, cases with positive LST but negative smear, can be related to the limited sensitivity of direct diagnostic methods rather than to LST sensitization due to exposure to parasite but with no clinical symptoms.…”
Section: Discussionsupporting
confidence: 63%
See 4 more Smart Citations
“…As in our study PCR assays have been carried out from smears' DNA, the molecular results were highly dependent on the samples collected and prepared for microscopy; and because P1+ smears had the lowest proportion of positive PCR (Figure 3), the importance of considering LST as a complementary diagnostic tool is highlighted. In a previous study, our group has shown that the ratio of positive LST to positive smear was ³ 1 and maintained across age groups, 19 supporting its diagnostic ability and suggesting that within an adequate epidemiologic frame, cases with positive LST but negative smear, can be related to the limited sensitivity of direct diagnostic methods rather than to LST sensitization due to exposure to parasite but with no clinical symptoms.…”
Section: Discussionsupporting
confidence: 63%
“…The results do not agree with recent research in the same study area in a larger group of patients. 19 No significant correlation was found for microscopic diagnosis and diameter of the lesion. The results agree with a previous work, where parasite burden was quantified by qPCR.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations